Dynamic simulation of the first cool down of the JT-60SA cryo-magnet system. (September 2022) - Michel, Frederic; Bonne, François; Fukui, Kazuma; Hamada, Kazuya; Hoa, Christine; Louzguiti, Alexandre; Natsume, Kyohei; Wanner, Manfred; Zani, Louis
Highlights: Results of the first cool-down of the JT-60SA cryo-magnet system. Development of SIMCRYOGENICS simulation models for the magnet cooling loops. Simulation of the JT-60SA cool-down and estimation of extracted power all along the cool-down. Comparison with good agreement between simulations and real JT-60SA cool-down. Abstract: In the framework of the Broader Approach research and development for fusion activities, involving Japan and Europe, the JT-60SA tokamak has been jointly constructed in Naka, Japan to support the operation of ITER and to study advanced plasma scenarios for future fusion power plants. The integrated commissioning of the tokamak started mid 2020 with a Japanese and European team, composed of QST, F4E and Eurofusion. CEA, as member of Eurofusion consortium, has brought expertise and support in the operation of the cryo-magnetic system. The cool-down from 300 K to 4.5 K took more than one month following stringent temperature constraints on the magnets and the thermal shields. Dynamic simulations models with Simcryogenics were developed during the cool down to support the magnet cool-down operation. Simcryogenics is the simulation library developed by CEA (Department of Low Temperature Systems) on a Matlab/Simulink platform for modelling cryogenic processes. This article presents the first cool-down of the JT-60SA magnet system and attempts to reproduce the measured data from 300 K to 4.5 K with the Simcryogenics models.